2006
DOI: 10.1111/j.1750-3841.2006.00182.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Lees Contact on Evolution of Amines in Chardonnay Wine

Abstract: Some white wines of Chardonnay variety are aged on their lees in oak barrels over several months. Over this period, autolysis takes place and different compounds are freed in the wine, among them, nitrogen compounds. The aim of this work was to study the evolution of amines in Chardonnay wine during 180 d of maturation on lees, with and without weekly stirring. The process was carried out in new French oak barrels with 225 L capacity. From the results obtained it was found that weekly stirring mainly had an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…After 135 days of wine ageing in barrel, all the nitrogen fractions decreased in the wines, both in the stirred wine and the unstirred wine, which could be due to secondary reactions of amino acid catabolism. These reactions involve the formation of amines and α‐keto acids from the amino acids and the conversion of these compounds to aldehydes, the reduction of the aldehydes to alcohols and/or their oxidation to acids constitutes the final reactions of amino acid transformation 14, 15. As regards the influence of the stirring on the concentration of total amino acids, amino nitrogen and assimilable nitrogen of the wines, differences were only observed in the concentrations of these parameters after 180 days of ageing, when the concentration of the nitrogen compounds was greater in the stirred wine than in the unstirred wine (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…After 135 days of wine ageing in barrel, all the nitrogen fractions decreased in the wines, both in the stirred wine and the unstirred wine, which could be due to secondary reactions of amino acid catabolism. These reactions involve the formation of amines and α‐keto acids from the amino acids and the conversion of these compounds to aldehydes, the reduction of the aldehydes to alcohols and/or their oxidation to acids constitutes the final reactions of amino acid transformation 14, 15. As regards the influence of the stirring on the concentration of total amino acids, amino nitrogen and assimilable nitrogen of the wines, differences were only observed in the concentrations of these parameters after 180 days of ageing, when the concentration of the nitrogen compounds was greater in the stirred wine than in the unstirred wine (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A decrease of tartaric acid after AOL has been observed [121], nonetheless, no significant differences were detected in the rest of the acids and titratable acidity. Other authors showed only minor differences in total acidity after 180 days of AOL in Chardonnay white wines [122].…”
Section: Cell Wall Polysaccharides From Non-saccharomyces Yeastsmentioning
confidence: 89%
“…So, the existing content of biogenic amines in wine will depend on the presence of precursor amino acids, LAB strains with decarboxylase activity, and environmental factors that affect the growth of these strains as well as some oenological practices [30,88,89]. In general, low pH and high concentrations of SO 2 and ethanol limit the growth of these strains and consequently the production of biogenic amines.…”
Section: The Formation Of Biogenic Aminesmentioning
confidence: 99%